A model of welfare competition with evidence from AFDC - Luz Amparo Saavedra (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
In this paper, we test empirically for strategic behaviour among the states using the cash support program Aid to Families with Dependant Children (AFDC). To motivate the empirical work, we adept Wildasins [41] model of income redistribution to a model of "interjurisdictional welfare competition." Although welfare competition may be generated from different frameworks, we choose Wildasins model to illustrate how welfare benefit interdependence is generated in the context of welfare migration. We estimate a "representative reaction function" for AFDC using both cross-sections and pooled cross-sections data. After controlling for other determinants of AFDC benefit levels and for spatial error autocorrelation, we find evidence showing competition.
Keywords: 330; Welfare competition; Sozialhilfe; Familienleistungsausgleich; Familienpolitik; Institutioneller Wettbewerb; Binnenwanderung; Schätzung; USA